ROLE CONCURRENT ENGINEERING TECHNOLOGY REDUCES AND IMPROVES PRODUCT LIFE CYCLE COSTS TO ACHIEVE AN INCREASE IN COMPETITION-AN APPLIED STUDY IN WASIT GENERAL COMPANY FOR TEXTILE INDUSTRIES - Marwah Jumaah Tuama (Scholar Express Journals, 2024)
The concurrent engineering technique is considered one of the important techniques in modern accounting because of its importance in improving product quality. This technique complemented the product life cycle costing technique and became an integrated model that helps reduce costs and develop the current product design model according to the customer’s requirements through the sum of the relative weights and the importance of each component on the basis of the relationship between customer requirements and component functionality. This research aims to show the cognitive foundations of the two techniques of product life cycle costing and concurrent engineering and their importance in achieving competitive advantage. Concurrent engineering technique has worked to reduce costs. and use program SPSS for investigation purpose Goals Research and verify its hypotheses Through this study, several conclusions were reached, the most important of which is :The concurrent engineering technique is the value engineering of an existing product to a new design that meets customer requirements by identifying components that need to be simplified and components that need to be enhanced .The research reached a set of recommendations, the most important of which are :Focus on using modern technologies and methods to reduce costs, which are compatible with the characteristics of the modern environment and appropriate to the nature of the work of the Or General Company for Engineering Industries and which are compatible with its cost structure. The most appropriate and best techniques should be chosen. The most appropriate technology that can be used at the present time is the technology of product life cycle cost management and simultaneous engineering because of their great benefit in managing and reducing costs and achieving competitive advantage.
Keywords: auditing profession; creative accounting